Face to face, person to person: Skills and attributes deployed by rural mental health clinicians when engaging with consumers. (December 2015) - Procter, Nicholas; Ferguson, Monika; Backhouse, Julia; Cother, Ingrid; Jackson, Adrian; Murison, Julie; Reilly, Julie‐Anne
Abstract: Objective: The purpose of this study was to identify the skills and attributes deployed by rural mental health clinicians when engaging with consumers in the community mental health context. Design: Reflecting the exploratory nature of this research, a semi‐structured focus group was conducted. Setting: One community mental health service in regional South Australia (catchment area = approximately 60 000 people). Participants: Nine mental health clinicians. Interventions: Not applicable. Main outcome measures: Participants' focus group comments were explored qualitatively using thematic analysis. Results: Three major themes were identified: (i) limitations to providing mental health care in the rural environment (increased consumer vulnerability, limited services, increased risk, and stigma); (ii) universal engagement approaches (being consumer‐focused, appropriate communication, facilitating a connection and normalising the experience); (iii) indicated and targeted strategies for engagement (flexible and creative delivery of care, a whole of community approach, being multiskilled and technology use). Conclusions: Although engaging with consumers involves many skills and attributes employed universally across mental health settings, the rural clinician's ability to navigate the environment and utilise this to provide consumer care is equally important to the engagement process. Specifically, these findings highlight the preference of rural mental health clinicians towards a person‐centred approach, networking with others in the community when providing care. Understanding how best to maximise the nature of a rural environment, such as facilitating relationships between clinicians and others in the community, will contribute to optimised care.